2019
DOI: 10.1071/wf18191
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the factors responsible for post-fire water quality response in forests of the western USA

Abstract: Wildfires commonly increase nutrient, carbon, sediment and metal inputs to streams, yet the factors responsible for the type, magnitude and duration of water quality effects are poorly understood. Prior work by the current authors found increased nitrogen, phosphorus and cation exports were common the first 5 post-fire years from a synthesis of 159 wildfires across the western United States. In the current study, an analysis is undertaken to determine factors that best explain post-fire streamwater responses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 50 publications
2
42
0
3
Order By: Relevance
“…While megafire had a clear and dominant influence on sediment dynamics, its effects on carbon and nutrients were more complex. Following observations from similar megafires [ 42 , 65 , 146 ], we hypothesized that increased nutrient availability and decreased nutrient demand in the terrestrial environment would result in higher lateral nutrient fluxes in burned watersheds. However, in contrast with previous research, which primarily focuses on burned-unburned comparisons in pristine watersheds [ 42 , 72 , 73 , 147 ], we found that the presence of urban and agricultural activity exerted a much greater influence on nutrient status than the megafire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While megafire had a clear and dominant influence on sediment dynamics, its effects on carbon and nutrients were more complex. Following observations from similar megafires [ 42 , 65 , 146 ], we hypothesized that increased nutrient availability and decreased nutrient demand in the terrestrial environment would result in higher lateral nutrient fluxes in burned watersheds. However, in contrast with previous research, which primarily focuses on burned-unburned comparisons in pristine watersheds [ 42 , 72 , 73 , 147 ], we found that the presence of urban and agricultural activity exerted a much greater influence on nutrient status than the megafire.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrological changes described above interact with the biological and physical changes caused by wildfires to affect solute and particulate chemistry in soil, surface water, and groundwater [ 42 , 57 , 65 ]. The loss of vegetation and soil organic matter during a wildfire can destabilize soils, leading to increased erosion rates that typically last around 5 years [ 56 , 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…Slow post-fire vegetation recovery likely dampens nutrient demand and retention and has been credited for persistent, elevated stream nutrients (Rhoades et al 2019). Here, Rust et al (2019) use publicly available stream water and wildfire data from more than 150 fires in the western US, and identified fire severity, post-fire vegetation recovery and site-specific soil properties as key contributors to post-fire stream nutrient and metal responses. The study by Williams et al (2019) examining the impacts of wildfire in the southern Canadian Rockies further demonstrates that the rate of vegetation recovery determines how long wildfires will alter precipitation inputs, which in turn drive the hydrologic processes that mobilise and transport potential contaminants.…”
Section: Contaminant Mobilisation and Transportmentioning
confidence: 99%
“…They also found that eroded C and N declined within a few years. There is, however, growing evidence that post-fire stream nutrient changes may persist longer where revegetation is slow (Rhoades et al 2019;Rust et al 2019) and there has been little effort to date to rehabilitate lingering wildfire effects using in-stream, riparian or upland rehabilitation treatments.…”
Section: Reducing Wildfire Impacts On Watersheds and Water Qualitymentioning
confidence: 99%
See 1 more Smart Citation